2014
DOI: 10.14411/fp.2014.040
|View full text |Cite
|
Sign up to set email alerts
|

Spathebothriidea: survey of species, scolex and egg morphology, and interrelationships of a non-segmented, relictual tapeworm group (Platyhelminthes: Cestoda)<sup>*</sup>

Abstract: * This paper is dedicated to Michael 'Mick' David Brunskill Burt (1938-2014 whose recent passing represents a great loss to cestodology.Abstract: Tapeworms of the order Spathebothriidea Wardle et McLeod, 1952 (Cestoda) are reviewed. Molecular data made it possible to assess, for the first time, the phylogenetic relationships of all genera and to confirm the validity of Bothrimonus Duvernoy, 1842, Diplocotyle Krabbe, 1874 and Didymobothrium Nybelin, 1922. A survey of all species considered to be valid is provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…In contrast, these molecular phylogenetic studies show that at least three Archigetes species are members of the most recently diverging caryophyllidean lineage, which comprises almost entirely Nearctic caryophyllideans [ 50 ]. The available data thus support the hypothesis that the monoxenic life cycle of Archigetes is a secondary abbreviation of the developmental cycle, similar to some spathebothriideans, such as Cyathocephalus truncatus (Pallas, 1781), Diplocotyle olrikii Krabbe, 1874 or Spathebothrium simplex Linton, 1922, whose maturation and egg production may occur in gammarid amphipods as their intermediate host [ 20 , 35 , 46 ].…”
Section: Introductionsupporting
confidence: 55%
“…In contrast, these molecular phylogenetic studies show that at least three Archigetes species are members of the most recently diverging caryophyllidean lineage, which comprises almost entirely Nearctic caryophyllideans [ 50 ]. The available data thus support the hypothesis that the monoxenic life cycle of Archigetes is a secondary abbreviation of the developmental cycle, similar to some spathebothriideans, such as Cyathocephalus truncatus (Pallas, 1781), Diplocotyle olrikii Krabbe, 1874 or Spathebothrium simplex Linton, 1922, whose maturation and egg production may occur in gammarid amphipods as their intermediate host [ 20 , 35 , 46 ].…”
Section: Introductionsupporting
confidence: 55%
“…The present study has shown that the anterior suckerlike organ of the Gyrocotylidea is a closed muscular invagination of the body tegument with an apical pore and somewhat resembles the anterior attachment organ of the spathebothriidean C. truncatus and the diphyllobothriidean S. bisulcatus, which belongs among the earliest derived branched of 'true' tapeworms (Eucestoda) (Waechenbach et al 2012, Kuchta et al 2014. If the gyrocotylidean anterior sucker-like organ is an indication of the previous presence of a digestive system in ancient ancestors of the Gyrocotylidea, such an organ may have been modified into a sucker-like attachment organ of the Eucestoda during cestode evolution.…”
Section: Phylogenetic Remarksmentioning
confidence: 72%
“…Bandoni and Brooks (1987) compared the anterior end of species of Gyrocotyle with the mouth of monogeneans that is rarely encircled by an oral sucker unlike that of digeneans (Fried and Haseeb 1991). The anterior organ (or acetabulum, or anterior pit) of species of Gyrocotyle looks like the mouth of monogeneans or an attachment sucker-like organ of some evolutionary early divergent tapeworms that possess a single apical anterior sucker-like organ (Riggenbach 1899, Fried and Haseeb 1991, Olson and Caira 2001, Kuchta et al 2014.…”
Section: Anterior Organ Of the Gyrocotylideamentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic interrelationships have been studied by Kuchta et al . (2014), and the most basal species seems to be the marine Spathebothrium simplex with a simple scolex without specialized attachment organs.…”
Section: Remarkable Achievementsmentioning
confidence: 99%